Inovasi Manajemen Sarana dan Prasarana PAUD dalam Menghadapi Era Pendidikan Hybrid: Analisis Kebutuhan dan Implementasi: Penelitian - Endi Ruhendi; Nasikin; Ahmad Syukron; Muji Raharjo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the needs and develop an innovation model for the management of facilities and infrastructure in Early Childhood Education (ECE) institutions in facing the challenges of hybrid learning in the digital era. This study employs a mixed methods approach with a sequential explanatory design, which combines quantitative and qualitative analysis in succession. Data were collected through observations, in-depth interviews, and document studies in five ECE institutions in Bekasi Regency that have implemented hybrid learning. The research findings indicate that 60% of early childhood education institutions still lack adequate digital infrastructure. Five key categories of essential facilities and infrastructure have been identified, including physical infrastructure, digital learning management systems, interactive technology devices, hybrid learning media, and integrated security systems. The implementation of the management innovation model is carried out through the stages of planning, organizing, executing, and evaluating. The impact of this implementation model shows a 37% increase in the efficiency of managing facilities and infrastructure and a 42% increase in children's engagement in hybrid learning.